A new species of Epeorus (Caucasiron) (Ephemeroptera, Heptageniidae) from Azerbaijan and Iran - Ľuboš Hrivniak (Pensoft Publishers, 2021)
A new species, Epeorus (Caucasiron) hyrcanicus sp. nov., is described based on larval morphology and molecular data (COI) containing sequences from all Caucasian Caucasiron species described to date. The species is distributed in the Hyrcanian forest of southeastern Azerbaijan and northwestern Iran. Based on our wide-range sampling, the new species is likely endemic to this area. The most pronounced larval morphological diagnostic characters are the coloration pattern of abdominal sterna (a pair of oblique stripes and stripe-like medio-lateral maculae) and terga (triangular medial maculae), poorly developed projection of the costal margin of gill plates III, presence of hair-like setae on the surface of abdominal terga, and relatively wide shape of gill plates VII (in natural position from ventral view). The diagnostic characters are compared to related species, and primary information to habitat is provided.